2016
DOI: 10.21013/jte.v5.n2.p2
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Appropriate Performance Measurement Framework for Total Quality Management (TQM) in Construction and Other Industries

Abstract: Total quality management (TQM) is a set of opinions and ideas that widely called "management philosophy". This management technique is able to assist the construction firms in improving

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Its main aims are to satisfy customers and survive in the market (Neyestani and Juanzon, 2016). Without doubt, quality experts (gurus) had the significant roles to expend and transform the concept of quality from a mere technical system to a broader body of knowledge known as total quality with management implications in production (Maguad, 2006).…”
Section: Quality Management Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its main aims are to satisfy customers and survive in the market (Neyestani and Juanzon, 2016). Without doubt, quality experts (gurus) had the significant roles to expend and transform the concept of quality from a mere technical system to a broader body of knowledge known as total quality with management implications in production (Maguad, 2006).…”
Section: Quality Management Systemsmentioning
confidence: 99%
“…Then Crosby, Feigenbaum, Ishikawa, and others had developed this powerful management technique for improving business quality within the organizations. During the period 1980s to 1990s, many national and international quality awards (QAs) have been established to provide guidelines for implementing TQM based on the suggestions and theories of QM gurus (Neyestani and Juanzon, 2016). The gurus extensively made substantial contribution to quality management by their theories in improving quality.…”
Section: A) Quality Gurusmentioning
confidence: 99%
“…Also, some researchers used only financial measures, others adopted many other operational performance indicators, whereas some measure the effectiveness of ISO 9001 standard on a set of the performance measures belonged to all main perspectives of performance (BSC) [17], [1]. Thus, in order to summarize and simplify the data analysis, the current study classified and discussed the effects of ISO 9001 on performance of the organizations in four main dimensions or perspectives of Balanced Scored (BSC), as suggested by Neyestani and Juanzon [20]. Then this study was categorized the production process (internal business process), customer's satisfaction, and innovation and growth as non-financial performance, and the discussions and conclusions related to the effects of ISO 9001 on Financial and non-financial were based on the aforementioned classifications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are different proposals for specific indicators in the construction industry (Lim, Jung, & Lee, 2015;Sarkar, Raghavendra & Ruparelia, 2015;Kim & Lee, 2015;Neyestani & Juanzon, 2016), among others. Specifically, in Latin America several investigations were conducted to improve the performance using indicators linked to business strategy (Costa, Formoso & Lantelme, 2002;, or defined a system of "benchmarking" based on performance indicators (Costa, Formoso, Kagioglou, Alarcón & Caldas, 2006;Ramirez, Alarcón & Knights, 2004), none of them specifically related to the production cycle of housing; in addition, no research has been found that surveyed a particular or specific model to integrate strategy, performance measurement, and traceability objectives using key performance indicators in developer and homebuilder companies.…”
Section: Introductionmentioning
confidence: 99%